Human Resources Development And Job Placement On Employee Job Satisfaction - Correa-Quezada, Ronny; Río-Rama, María de la Cruz del; Quoc, Anh Nguyen (Journal of Management, 2022)
This study sought to quantify the impact of job placement and human resource development on employee work satisfaction at the PT Bina Administrative Branch of the Videotron Bandung Division. Descriptive and associative research with a quantitative approach was the strategy used in this study. 37 employees were employed as samples in this study, which used saturated sampling as its sampling method. Validity and reliability tests, multiple linear regression with correlation coefficients, determination, research model testing, and research hypothesis testing were all employed in data analysis approaches. The development of human resources and job placement influence employee work satisfaction by 67.4%, according to the study's coefficient of determination test (R2) results, with additional factors outside of this study influencing the remaining 32.6%. According to the multiple correlation coefficient test, the R value of 0.674 indicates that there is a very strong association between employee job satisfaction and human resource development and job placement. The F test's findings, specifically the value of 14.584>3.26, show that Fcount is bigger than Ftable. Workplace placement and human resource development factors have a favorable and significant impact on employees' job satisfaction.